Viking Ghost Hunt: creating engaging sound design for location–aware applications. (3rd December 2012) - Paterson, Natasa; Kearney, Gavin; Naliuka, Katsiaryna; Carrigy, Tara; Haahr, Mads; Conway, Fionnuala
In this paper, we present and describe the sound design and audio evaluation of Viking Ghost Hunt, a location–aware game based around important historical locations in Dublin, Ireland. We describe the novel approach taken in developing an engaging soundscape for location–aware games in mobile multimedia devices that highlight the importance of spatial audio and reverberation in the subjective sensation of engagement with the game. In particular, we present how the level difference and temporal separation between the direct sound of the sound object, the early reflections and the diffuse reverberant field influence this engagement. Results obtained from this investigation in regards to reverberation and engagement may therefore inform future location–aware sound designs.